India's policy stance on reserves and the currency - Ila Patnaik (Indian Council for Research on International Economic Relations (ICRIER), 2003)
Over the last decade, India engaged in substantial liberalisation on the current account and the capital account. At the same time, a fully articulated policy framework defining the currency regime is not known in the public domain. In this paper, we seek to characterise then ature of the currency regime, in the period after the Asian crisis. This is closely linked to better understanding the phenomenon of reserves accumulation of the recent years. Our results suggest that the main focus of the currency regime has been to deliver a low volatility of the nominal exchange rate. The rupee appears to be a de facto peg to the USD. In the last one year, reserves accumulation cannot be explained by insurance motivations; it seems to be a passive side effect of maintaining the currency regime
Keywords: 330